The Freedom of Testamentary Disposition in the Macedonian Succession Law - Angel Ristov (Iustinianus Primus Law Review, 2013)
One of the basic characteristics of the continental law is the limited freedom of testamentary disposition. The Macedonian succession law belongs to the continental tradition that envisages the limited freedom of testamentary disposition. In this paper, the author analyses the freedom of testamentary disposition in the current Macedonian succession law with the aim to determine the limits of its application and the need for changes of the existing legislation by giving concrete proposals and solutions.
Keywords: freedom of testamentary disposition, testamentary succession, will, forced share